Succulent wild love : six powerful habits for feeling more love more often - Sark, 1954- (New World Library, 2015)
"Succulent Wild Love by SARK and Dr. John Waddell is a truly revolutionary book about expanding the love in your life and having the skills and tools to keep love flowing. Everyone wants to feel more love more often. This book shows you exactly how to do that and keep doing it. For years SARK has filled her cup of self-love and shared the overflow with others. Through SARK's vulnerability, insight and colorful out-of-any-box explorations in books such as Succulent Wild Woman, Transformation Soup and Eat Mangoes Naked, readers have been inspired to accept and love themselves. From that foundation, SARK is now expanding her self-love capacities to include a deep, intimate relationship with another. This book shares her transformative journey and shows readers how they can do the same with the significant others in their lives. For much of her life SARK feared committing to a life partnership, even as she was looking for ever more expansive ways to share her love. In this book, with delightful art and sharing intimate experiences, SARK illuminates the fears and obstacles that kept her--and keep many others--from living happily in intimate partnerships. Using stories of transformation and practical advice, SARK and her partner, clinical psychologist and spiritual teacher Dr. John Waddell, present six simple but profound habits that will empower readers to keep their relationships harmonious--and from that foundation, help them experience more love more often. Rather than emphasizing finding the right partner, Succulent Wild Love focuses on being the right partner. If you are looking for someone to make you happy, they will always fall short. If you are looking for someone with whom to share your happiness, you will always have enough. Succulent Wild Love is an inviting book that is both practical and magical, filled with effective guidelines and SARK creativity. There are real-life, insightful stories and innovative ways for the reader to play and practice, SARK's trademark poetry and art, along with the logical psychological principles that Dr. Waddell provides. This combination reminds readers that they already are Succulent, Wild and Loving -- and can experience feeling that way more often"--